The Effect of Work Spirit and Service Climate Organization on Employment Engagement and Their Impact on Organizational Citizenship Behavior (OCB) (Study on Employees of PT. Adhi Persada Beton Jakarta) - Niken Ayu Pebriola; Lieli Suharti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the effect of Work Spirit and Service Climate Organizational on Work Engagement and its impact on Organizational Citizenship Behavior (OCB) for employees of PT. Adhi Persada Beton Jakarta. The method used is a quantitative method, which aims to determine the effect of two or more variables. The analytical technique used is path analysis technique and the goodness of fit test using the Shumacker & Lomax formula with the trimming level of significance 5%. The variables in this study are Work Spirit (X1), Service Climate (X2), to work engagement (Z) and its impact on Organizational Citizenship Behavior (OCB) (Y). Data was analyzed using SPSS 24.0 for the Windows program. The results of this study indicate that work morale has a positive effect on work engagement, then service climate organization positive effect on work engagement, while work engagement positive effect on Organizational Citizenship Behavior (OCB). Then Work Attachment has a positive effect on Organizational Citizenship Behavior (OCB). Meanwhile, Work Spirit has no effect on Organizational Citizenship Behavior (OCB) through Work Engagement, and Organizational Service Climate has no effect on Organizational Citizenship Behavior (OCB) through Work Engagement.